Modeling the Effect of using the Sports video games on Sports consumption - Sh. Shafiee; H. Rostami; H. Afrouzeh; A. Ashouri (Taḥqīqāt-i Farhangī-i Īrān)
The purpose of this study was to investigate the effects of using the sports video games on sports consumption. The research method was descriptive-survey and of applied type. The required information was also collected through a questionnaire. The statistical population of this study included all high school students including 3rd, 7th, 8th and 9th grade in city of Rasht. The research sample was 183 people. In this research, data were collected through the questionnaire and then analyzed with PLS2 software. The results of the research showed that the conceptual model of the research has a desirable fit (GOF= 0.41). Based on the results, there is a significant direct relationship between sports fan and using the sports video games (r = 0.49, t = 10.87), and between sports fan and sports consumption (r = 0.45, t= 9.77). Moreover, there is a significant indirect relationship between sports video games and sports consumption with the mediating role of sports fan (r = 0.41, t= 4.73). As a result, sports marketers should encourage sports video games as a strategy for increasing sports consumption, especially among those who are less known as sports fan.